MEAT AND MEAT PRODUCTS MARKET IN RUSSIA: CURRENT STATE AND DEVELOPMENT PROSPECTS - Alexey V. Puzakov (Статистика и экономика, 2016)
Article features statistical analysis of current state and prospects of meat and meatproducts market in Russia in the conditions of unstable environment. The role of meat production in the context of foodsecurity in Russia is characterized, thebasic guidelines for ensuring food securityin the ﬁeld of meat and meat products aresystematized. According to the dynamics of meat production in Russia, Box-Jenkinsseasonal model was constructed. Short-term forecasts of meat production werecalculated on the base of the model.